Intellectual Property in the EU-MERCOSUR FTA: A brief review of the negotiating outcomes of a long-awaited agreement - Roxana Blasetti; Juan I. Correa (South Centre, 2021)
This paper provides a first glance at the Intellectual Property Chapter of the Free Trade Agreement (FTA) between the Southern Common Market (MERCOSUR) and the European Union (EU). It is not intended to provide an exhaustive analysis of the commitments involved but rather to briefly review the scope of intellectual property in the bi-regional negotiations, which took more than 20 years and ended in June 2019 with an “agreement in principle.” It also aims to put the Chapter into context with the whole commitments covered by the FTA and, finally, to highlight its most relevant aspects.
Keywords: 300; Biodiversity; Border Enforcement; Copyright; Disclosure; European Union (EU); Exhaustion; Free Trade Agreements (FTAs); Geographical Indications; Industrial Designs; Intellectual Property; Intellectual Property (IP) Enforcement; Level of Protection; MERCOSUR; National Treatment; Patent; Plant Variety Protection (PVP); Public Health; Trademarks; Traditional Knowledge; TRIPS; TRIPS Plus